2013
DOI: 10.1002/eat.22096
|View full text |Cite
|
Sign up to set email alerts
|

Executive functioning and behavioral impulsivity of young women who binge eat

Abstract: Objective: To examine the link between binge eating, executive functioning, and behavioral impulsivity.Method: Fifty women who reported engaging in weekly binge eating in the absence of regular compensatory behaviors and 66 women with no history of binge eating completed several self-report questionnaires and a brief neuropsychological battery, including the Wisconsin Card Sorting Task and Conner's Continuous Performance Task.Results: Hierarchical regression analyses revealed that groups did not differ in exec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 96 publications
2
40
1
3
Order By: Relevance
“…With regard to the first of the five dispositions, sensation seeking, results suggest that individuals with eating disorders characterized by binge eating and/or purging behaviors tend to display elevated sensation seeking, whereas those with restrictive eating disorder presentations tend to display lower levels [5,6,14,15]. Further, in a meta-analytic review of impulsivity facets in relation to bulimic symptoms, sensation seeking was found to demonstrate a significant effect size [1].…”
Section: Five Facets Of Impulsivity In Eating Disordersmentioning
confidence: 93%
See 1 more Smart Citation
“…With regard to the first of the five dispositions, sensation seeking, results suggest that individuals with eating disorders characterized by binge eating and/or purging behaviors tend to display elevated sensation seeking, whereas those with restrictive eating disorder presentations tend to display lower levels [5,6,14,15]. Further, in a meta-analytic review of impulsivity facets in relation to bulimic symptoms, sensation seeking was found to demonstrate a significant effect size [1].…”
Section: Five Facets Of Impulsivity In Eating Disordersmentioning
confidence: 93%
“…Regarding the second and third dispositions, lack of planning and lack of perseverance, respectively, existing findings have been mixed. Some research suggests that those with bulimic spectrum disorders show no differences from controls in terms of these constructs [15]. Studies that have examined concurrent and prospective associations between these constructs and eating disorder symptoms have also had inconsistent findings [e.g., [16][17][18][19].…”
Section: Five Facets Of Impulsivity In Eating Disordersmentioning
confidence: 99%
“…Based on this theory, individuals with difficulties tolerating negative affect and/or a propensity to respond to these emotions impulsively might also be more likely to binge eat. Indeed, negative urgency, or the tendency to act impulsively when distressed, has been linked to increases in binge eating among women in most, but not all (Peterson & Fischer, 2012), longitudinal (Fischer, Peterson, & McCarthy, 2013;Pearson, Combs, Zapolski, & Smith, 2012) and cross-sectional studies (Anestis, Selby, Fink, & Joiner, 2007;Carrard, Crépin, Ceschi, Golay, & Van der Linden, 2012;Fischer, Anderson, & Smith, 2004;Fischer, Settles, Collins, Gunn, & Smith, 2012;Fischer, Smith, & Cyders, 2008;Kelly, Bulik & Mazzeo, 2013). General difficulties tolerating distress have also been linked to increases in binge eating behavior (Corstorphine, Mountford, Tomlinson, Waller, & Meyer, 2007) beyond the influence of depressive symptoms, anxiety, general negative affect, and disordered eating attitudes (Anestis et al).…”
Section: Introductionmentioning
confidence: 95%
“…However, we did not find support for this idea, as core ADHD symptoms in childhood were not associated with later binge eating in adolescence. Impulsivity has previously been linked with binge eating 31,32 ; however, we could not study this association because of a lack of data on impulsivity. Furthermore, it may be possible that ADHD symptoms are associated with other disordered eating patterns that are not measured here.…”
Section: Discussionmentioning
confidence: 97%
“…Some evidence suggests an association between binge eating and behavioral impulsivity. 31,32 A recent study found that symptoms of ADHD were significantly, but not differentially, greater in obese patients with and without binge eating behaviors. 33 Therefore, the extent to which obesogenic behaviors underlie the ADHD-obesity association is unclear.…”
mentioning
confidence: 99%